Production and utilization of pyrolysis oil from solidplastic wastes: A review on pyrolysis process and influence of reactors design. (15th January 2022) - Sekar, Manigandan; Ponnusamy, Vinoth Kumar; Pugazhendhi, Arivalagan; Nižetić, Sandro; Praveenkumar, T.R.
Abstract: This paper reviews the new progress, challenges and barriers on production of pyrolysis oil from the plastic waste. Among the different processes thermal and catalytic are the potential methods to produce oil. Since the global plastic production increased over years the accumulation of plastic waste increases. Thus, converting the waste plastics into useful energy is very essential to avoid the environmental concerns. Initially the thermal pyrolysis process and its advantage on production of pyrolysis oil were discussed. During the thermal decomposition the waste plastic had been converted into the products such as gas, crude oil and solid residues. Secondly, the catalytic process and its recent trends were discussed. In addition, the factors affecting the catalytic pyrolysis process had been evaluated. Furthermore, the optimized concentration of catalyst subjected to the higher yield of fuel with low hydrocarbon content was found. The pyrolysis oil produced from the catalytic process has higher heating values, lower density and lower viscosity compared to thermal process. In addition, the application of pyrolysis oil on the diesel engines had been discussed. The effects of pyrolysis oil on combustion and emission characteristics were observed. This review summarizes the potential advantages and barriers of both thermal and catalytic process. Further, the optimized solutions and applications of pyrolysis oil are suggested for sustainability of the process. Besides the introduction of the pyrolysis oil were viable without making major modification to the existing engine design. Highlights: Impact of the pyrolysis oil by the catalytic and non-catalytic process are reviewed. Sustainability of the pyrolysis oil in diesel engine was examined. The effects of the synthetic and natural zeolites are emphasized. Challenges and the barriers for the production of cheap bio-oil were presented. Combustion and emission characteristics are improved for catalytic pyrolysis oil.